UPAYA PENGUATAN âMOTIVASI BERAKHLAKUL KARIMAHâ TERHADAP PESERTA DIDIK BERIBU NENEK DENGAN PEMBELAJARAN KITAB TAâLIM MUTAâALIM (Studi di MTs Plus Nururrohmah Tambaksari Kuwarasan Kebumen, Jawa Tengah) - Rahmatullah, Azam Syukur (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2016)
The students who has grand mother as mother Â were in danger on moral. The students were only controlled by the grand mothers, and it made less education. The grand mothers were too over on giving love, it made the students were spoiled and they did deviant behavior. The Islamic Secondary School Nururohmah has many students who have grand mother as mother did a special way on educating students by understanding Kitab Taâlim Mutaâalim. The results showed that the students more open minded and aware to do the right thing.Â Keywords: Students, Grand Mother as Mother, Kitab Taâlim Mutaâalim Islamic Secondary School NururohmahÂ  Â